Global media, culture, and identity : theory, cases, and approaches - Gajjala, Radhika, 1960-; Chopra, Rohit (Routledge, 2011)
This edited volume examines the ways that global media shapes relations between place, culture, and identity. Through the included essays, Chopra and Gajjala offer a mix of theoretical reflections and empirical case studies that will help readers understand how the media can shape cultural identities and, conversely, how cultural formations can influence the political economy of global media. The interdisciplinary, international scholars gathered here push the discussion of what it means to do global media studies beyond uncritical celebrations of the global media technologies (or globaliza.